ANALISIS FENOMENA GERAKAN WOMEN'S MARCH DAN RESPON MEDIA - Rifqi, Reino Auzan (JURNAL LENTERA : Kajian Keagamaan, Keilmuan dan Teknologi, 2022)
ABSTRACT Women's March is used as a media frame because as a feminist movement that extends throughout the world. The media that will be used are CNN, Al-Jazeera and USAToday, the aim is to examine the media packages used by the three media sources in the Women’s March phenomenon. The theory is used with media framing and feminism. The methodology is using descriptive qualitative research. The result is a media frame against Women 's March with a positive picture because the media portray Women' s March as a social change that is very influential and brings the attention of many people even though there is little political element. Therefore, the implication is that every news sources has its own agenda and bias. Keywords: framing media, feminism, media sources.